The ichnogenus Lapispira from the Early Jurassic of Patagonia (Chubut, Argentina) - Pagani, María Alejandra (2012)
The ichnogenus Lapispira Lange (originally recognized in the Hettangian of Germany) attained a wide geographic distribution, occurring mainly in Jurassic sediments. The ichnotaxon was recently re-described in Sinemurian-Pliensbachian deposits in southern Mendoza Province (Argentina), and is here newly reported in slightly younger (latest Pliensbachian) deposits of the Mulanguiñeu Formation of Chubut Province. According to recent revisions, the ichnogenus appears to have been mainly environmentally restricted to the shoreface and offshore-shoreface transition zone, being only exceptionally found in offshore tempestites. In Chubut Lapispira bispiralis Lange is accompanied by an abundant euhaline fauna dominated by bivalves, several gastropods and rare ammonoids , and, similarly to what happens in the Neuquén Basin, it is commonly associated to Rhizocorallium isp.